Concentration‐QT modelling of the novel DHFR inhibitor P218 in healthy male volunteers. Issue 1 (9th July 2021) - Täubel, Jӧrg; Lorch, Ulrike; Ferber, Georg; Spencer, Christopher S.; Freier, Anne; Coates, Simon; El Gaaloul, Myriam; Donini, Cristina; Chughlay, Mohamed Farouk; Chalon, Stephan
Abstract : Aims: Given the increasing emergence of drug resistance in Plasmodium, new antimalarials are urgently required. P218 is an aminopyridine that inhibits dihydrofolate reductase being developed as a malaria chemoprotective drug. Assessing the effect of new compounds on cardiac intervals is key during early drug development to determine their cardiac safety. Methods: This double‐blind, randomized, placebo‐controlled, parallel group study evaluated the effect of P218 on electrocardiographic parameters following oral administration of seven single‐ascending doses up to 1000 mg in 56 healthy volunteers. Participants were randomized to treatment or placebo at a 3:1 ratio. P218 was administered in the fasted state with standardized lunch served 4 hours after dosing. 12‐lead ECGs were recorded in triplicate at regular intervals on the test day, and at 48, 72, 120, 168, 192 and 240 hours thereafter. Blood samples for pharmacokinetic evaluations were collected at similar time points. Concentration‐effect modelling was used to assess the effect of P218 and its metabolites on cardiac intervals. Results: Concentration–effect analysis showed that P218 does not prolong the QTcF, J‐Tpeak or TpTe interval at all doses tested. No significant changes in QRS or PR intervals were observed. Two‐sided 90% confidence intervals of subinterval effects of P218 and its metabolites were consistently below the regulatory concern threshold for all doses. Study sensitivity was confirmed by significant shortening of QTcF after a meal. Conclusion: Oral administration of P218 up to 1000 mg does not prolong QTcF and does not significantly change QRS or PR intervals, suggesting low risk for drug‐induced proarrhythmia.